2009
DOI: 10.1172/jci38854
|View full text |Cite
|
Sign up to set email alerts
|

Smad4 loss in mice causes spontaneous head and neck cancer with increased genomic instability and inflammation

Abstract: Smad4 is a central mediator of TGF-β signaling, and its expression is downregulated or lost at the malignant stage in several cancer types. In this study, we found that Smad4 was frequently downregulated not only in human head and neck squamous cell carcinoma (HNSCC) malignant lesions, but also in grossly normal adjacent buccal mucosa. To gain insight into the importance of this observation, we generated mice in which Smad4 was deleted in head and neck epithelia (referred to herein as HN-Smad4 -/-mice) and fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
310
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(337 citation statements)
references
References 54 publications
22
310
0
3
Order By: Relevance
“…This function may be correlated with the decreased expression of TβR I, TβR II and common-mediator Smads (Smad4), which limit the downward propagation of the TGF-β1/Smad4 signal and subsequently cause tumor growth inhibition to reduce or even become deficient. Certain animal experiments and clinical studies (28)(29)(30)(31) have also revealed that, within the tumor, several types of mutations in the TβR II and Smad4 genes have been identified. The loss of TβR II function may cause tumor cells to deregulate the expression of the receptor protein, obstruct the transmission of the TGF-β1 growth inhibiting signal (32) and subsequently display malignant proliferation and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…This function may be correlated with the decreased expression of TβR I, TβR II and common-mediator Smads (Smad4), which limit the downward propagation of the TGF-β1/Smad4 signal and subsequently cause tumor growth inhibition to reduce or even become deficient. Certain animal experiments and clinical studies (28)(29)(30)(31) have also revealed that, within the tumor, several types of mutations in the TβR II and Smad4 genes have been identified. The loss of TβR II function may cause tumor cells to deregulate the expression of the receptor protein, obstruct the transmission of the TGF-β1 growth inhibiting signal (32) and subsequently display malignant proliferation and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Absence of or decreased SMAD4 expression has been found in various cancers, including pancreatic, colorectal, head and neck (Bornstein et al 2009, Ikushima & Miyazono 2010, and more recently found in papillary thyroid carcinomas (D'Inzeo et al 2010). These results provide evidence that the TGFb signaling pathway functions as a tumor suppressor that cancers must bypass for their progression.…”
Section: Introductionmentioning
confidence: 53%
“…Loss of β2SP is observed in human HCC 14, 61, 62, 63. Evidence from Smad4‐knockout mice, which develop head and neck cancers, demonstrates a significant role for Smad4 in promoting genomic stability 64. Another piece of evidence from studies of liver regeneration that implicates TGF‐β pathway in cancer involves vitamin D deficiency.…”
Section: Liver Stem Cells and Tgf‐β: Evidence From Mouse Knockout LImentioning
confidence: 99%
“…Keratinocytes cultured from TGF‐β1–null mice have marked genomic instability that could accelerate tumor progression 68. More recently, studies have been conducted in Smad4 conditional knockout mice that develop head and neck cancers, where Smad4 has been postulated as a “guardian of the genome” through regulation of the Fanconi anemia/Brca (Fanc/Brca) DNA repair pathway 64, 69. Interestingly, the development of HCCs in β2SP heterozygote mutants establishes β2SP as a nontraditional and functional tumor suppressor.…”
Section: Liver Stem Cells and Tgf‐β: Evidence From Mouse Knockout LImentioning
confidence: 99%